DESIGN & ANALYSIS OF CONNECTING ROD BY COMPOSITE MATERIAL - kumar, A.Prem (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
Connecting rod is one of the important components of the whole engine assembly as it acts as a mediator between piston assembly and crankshaft. Its converting the reciprocating motion of the piston to rotary motion of the crank. Also it faces a lot of tensile and compressive loads during its life time. Generally connecting rods are manufactured using carbon steel and in recent days aluminium alloys are finding its application in connecting rod. In this work connecting rod is replaced by aluminium based composite material reinforced with Boron carbide. And it also describes the modelling and analysis of connecting rod. Proe solid modeling software is used to generate the 3-D solid model of Connecting rod. Ansys software is used to analyze the connecting rod. The main aim of the project is to analysis the stress, strain, deformation of connecting rod by varying material with same geometry.